Trish Griffin, Dancing on the Head of a Pin: Reflections on the Camino - Scott, Jamie S (Journal for the Academic Study of Religion, 2022)
Trish Griffin, Dancing on the Head of a Pin: Reflections on the Camino. Kiama, NSW: AIA Publishing, 2020, pp. 158. Colour photographs. ISBN: 9781922329059 (pbk). AU29.70; US28.43.